The Art of Investigation - A. Binns, Chelsea; Sackman, Bruce (CRC Press, Taylor & Francis Group, 2021)
The Art of Investigation examines the qualities required to be a professional, thorough, and effective investigator. As the title suggests, it delves into more than the steps and procedures involved in managing an investigation, but the "soft" skills necessary to effectively direct and intuit along the way. The editors, and contributing authors, are the best in their field and bring a wealth of real-world knowledge and experience to the subject. There are several publications available on the nuts-and-bolts of the process and stages of an investigation. That ground has been covered. However, little has been published on the investigative skills required, the traits necessary, and the qualities endemic to an inquisitive mind that can be cultivated to improve an investigator's professional skill-set. Each chapter discusses the applicability of the traits, and requirements to the contributors' own work and experience as an investigator. In doing so, the contributors provide a story-or set of stories-from their personal experience which demonstrates their use or a given trait and its importance in the course of their investigative work and career. This will be first-hand experience that will serve to help any investigative profession in the course of their work. The case examples included throughout are sometimes surprising, but always engaging and insightful. An investigator must keep an open mind above all else and this book will seek to "lift the veil" on the inner workings of an investigation in addition to the thought process and inner monologue of an investigator as part of that process